A non‐canonical role of the p97 complex in RIG‐I antiviral signaling - Hao, Qian (EMBO J, 2015)
RIG‐I is a well‐studied sensor of viral RNA that plays a key role in innate immunity. p97 regulates a variety of cellular events such as protein quality control, membrane reassembly, DNA repair, and the cell cycle. Here, we report a new role for p97 with Npl4‐Ufd1 as its cofactor in reducing antiviral innate immune responses by facilitating proteasomal degradation of RIG‐I. The p97 complex is able to directly bind both non‐ubiquitinated RIG‐I and the E3 ligase RNF125, promoting K48‐linked ubiquitination of RIG‐I at residue K181. Viral infection significantly strengthens the interaction between RIG‐I and the p97 complex by a conformational change of RIG‐I that exposes the CARDs and through K63‐linked ubiquitination of these CARDs. Disruption of the p97 complex enhances RIG‐I antiviral signaling. Consistently, administration of compounds targeting p97 ATPase activity was shown to inhibit viral replication and protect mice from vesicular stomatitis virus (VSV) infection. Overall, our study uncovered a previously unrecognized role for the p97 complex in protein ubiquitination and revealed the p97 complex as a potential drug target in antiviral therapy.